Modulations of visual and somatosensory perception by action - Nam, Se-Ho (2011)
This thesis aimed to further investigate the effects of movements on modulations of visual and somatosensory perception. The first experiment (Chapter 2) investigated spatial mislocalisation of visual stimuli presented before saccade using a pointing paradigm and found that a predictive remapping of visual space occurred before saccade and the post-saccadic remapping employed spatially as well as temporally accurate memory of pre-saccadic visual stimuli. The second experiment (Chapter 3) examined relevance of saccadic chronostasis to remapping of visual space using a target displacement paradigm and found that it did not serve as a mechanism that fills in a perceptual gap during saccadic suppression. The third (Chapter 4) and fourth (Chapter 5) experiments adopted a target blanking paradigm and found that the pre-saccadic stimuli predictively remapped before saccade were anchored to the location of the pre-saccadic target remapped using a precise efference copy and neither saccade landing sites nor remembered locations of pre-saccadic targets were used in this process. Behavioural (Chapter 6) and fMRI (Chapter 7) studies were conducted to investigate modulations of tactile perception by manual movements and found that the tactile attention induced by the cued index finger facilitated processing of tactile stimuli presented to the responded hand. The somatosensory ROIs mainly showed a bias towards contralateral tactile stimulation in comparison with ipsilateral tactile stimulation. The right primary motor cortex (right M1), the left precuneus (left PreC) and the left middle frontal gyrus (left MFG) showed significant modulations of somatosensory processing by the Moving condition compared to the Non Moving condition. The final chapter included summaries and conclusions of each chapter and proposals for future investigations.